Occurrence of deformed wing virus variants in the stingless bee Melipona subnitida and honey bee Apis mellifera populations in Brazil. (10th January 2019) - de Souza, Flaviane S.; Kevill, Jessica L.; Correia-Oliveira, Maria E.; de Carvalho, Carlos A. L.; Martin, Stephen J.
Abstract : The global spread of the parasitic Varroa mite has introduced a new bee to the bee horizontal transmission route for several RNA viruses that bypasses existing barriers in honey bees. From among these viruses, deformed wing virus (DWV) is now among the most widespread insect pathogens in the world. Brazilian stingless bees are a diverse group often managed in close proximity to honey bees. Therefore, we investigated the prevalence and load of DWV in 21 stingless bee ( Melipona subnitida ) and 26 honey bee ( Apis mellifera ) colonies from Brazil. DWV was detected in all colonies with DWV-A and DWV-C dominating in M. subnitida, while DWV-A dominated in A. mellifera . Average total viral loads per bee were 8.8E+07 and 6.3E+07 in M. subnitida and A. mellifera, respectively, which are much lower than DWV levels (>1E+10) found in honey bees in the northern hemisphere. In colonies introduced 30 years ago to the remote island of Fernando de Noronha, the DWV load was low (<1E+03) in honey bees but we detected higher loads (1.6E+08) in all M. subnitida colonies on the island. This may suggest that minimal, if any, viral transmission of DWV from stingless bees to honey bees has occurred on this island. Furthermore, the ubiquitous presence of the DWV-C variant in M. subnitida colonies, and its rarity in A. mellifera, may again suggest that limited viral exchange between these two species is occurring.